2006
DOI: 10.1007/s11010-005-9088-0
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of crocetin in accordance to tumor incidence, antioxidant status, drug metabolizing enzymes and histopathological studies

Abstract: Lung cancer is the leading cause of cancer related mortality worldwide. Crocetin, saffron plant derivative known to play a role in cancer chemoprevention. In the present study the effects of crocetin was tested against lung cancer-bearing mice in both pre-initiation and post-initiation periods. Healthy male Swiss albino mice (6-8 weeks old) were used throughout the study. Experiment was designed with the treatment regimen of crocetin [20 mg/kg body weight dissolved in dimethyl sulphoxide (DMSO)] for 4 weeks be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 42 publications
5
63
0
4
Order By: Relevance
“…A previous study has shown that crocetin suppresses TPA-induced expression of oncogenes in the mouse epidermis and inhibits TPA-induced skin carcinogenesis [23] . Another in vivo study has shown that crocetin displays antitumor activities in a lung cancer animal model by scavenging free radicals [24] . Because p53 is mutated in approximately 50% of human tumors, we selected three cancer cell lines with different statuses of p53 to study the anticancer effects of crocetin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that crocetin suppresses TPA-induced expression of oncogenes in the mouse epidermis and inhibits TPA-induced skin carcinogenesis [23] . Another in vivo study has shown that crocetin displays antitumor activities in a lung cancer animal model by scavenging free radicals [24] . Because p53 is mutated in approximately 50% of human tumors, we selected three cancer cell lines with different statuses of p53 to study the anticancer effects of crocetin.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal experiments have shown that high doses of crocetin in vivo are well-tolerated and relatively nontoxic with a potential to exert anticancer activities [11,14,24] . These data indicate the possibility that crocetin may be used at relatively high doses for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the impact of saffron carotenoids on human health is due to their high antioxidant capacity which was investigated by many researchers (Makhlouf et al 2011;Asdaq and Inamdar 2010;Karimi et al 2010;Bathaie and Mousavi 2010;TavakkolAfshari et al 2008;Kanakis et al 2007;Soeda et al 2007;Magesh et al 2006;Ochiai et al 2004;Selim et al 2000;Verma and Bordia 1998;Nair et al 1995). One of hypothesis for the modes of anti carcinogenic and anti tumor actions of saffron has been proposed the inhibitory effect on free radical chain reactions (Makhlouf et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…8) Crocetin is a saffron plant carotenoid, which acts in various ways on biological system, numerous studies have demonstrated a variety of pharmacological actions for crocetin. [8][9][10] Therefore an attempt was made to study the modulating role of crocetin in lung mitochondria. The eight and eighteen weeks of crocetin treatment was used to study the oxidative mitochondrial dysfunction of B[a]p in the experimental animals.…”
mentioning
confidence: 99%